2023
DOI: 10.1007/s00520-023-07716-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of exercise for pain management in adults living with and beyond cancer: a systematic review and meta-analysis

Abstract: Background Pain is a common side effect of cancer or cancer treatment that negatively impacts biopsychosocial wellbeing and quality of life. Exercise is a potential intervention to manage pain that is safe and has multiple benefits. The objective was to determine the role of exercise in cancer pain management. Methods We completed a systematic review and meta-analysis of exercise interventions in adults with any type or stage of cancer by searching Ovid MEDLINE®, Embase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 124 publications
(135 reference statements)
0
6
0
Order By: Relevance
“…These factors make home-based exercise, streaming-based programs a resource to consider in exercise recommendation. Therefore, it is an alternative to offer guided and supervised exercise programs to a larger population, as confirmed by other researchers (26,27).…”
Section: Discussionmentioning
confidence: 54%
“…These factors make home-based exercise, streaming-based programs a resource to consider in exercise recommendation. Therefore, it is an alternative to offer guided and supervised exercise programs to a larger population, as confirmed by other researchers (26,27).…”
Section: Discussionmentioning
confidence: 54%
“…Regarding the effects of PE on treatment-related pain in cancer patients, the available studies suggest that resistance training or combined resistance-endurance training may contribute to pain relief ( 50 , 51 ). However, a recent review and meta-analysis found the overall risk of bias for most studies was rated as some concern and the grading of evidence certainty was low ( 52 ). It is possible that endurance and/or resistance training with blood flow restriction could also have beneficial effects in patients with CML suffering from chronic pain, as has been shown in other patient cohorts ( 53 , 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…Six systematic reviews 93 , 94 , 95 , 96 , 97 and 19 new RCTs 59 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 were newly identified in addition to the 2 prior RCTs in the 2019 ACSM Roundtable Guidelines. 116 , 117 Across the 21 RCTs, 12 studies targeted patients with breast cancer, 2 hematologic, 4 were conducted in mixed populations, and one study each focusing on head/neck/thyroid, esophageal, and prostate.…”
Section: Resultsmentioning
confidence: 99%